Plan de marketing digital para potencializar el turismo en el cantón Portoviejo - Zambrano Mera, Omairys Dalena (2023)
The present investigation had as its main objective the elaboration of a digital marketing plan to potentiate tourism in Portoviejo canton, for this reason a methodology with a mixed approach (Qualitative-Quantitative) was proposed, which consisted of four phases, in the first one A situational diagnosis was carried out to know the characteristics of the study area, in the second phase a market study was prepared to analyze supply, demand and competition, in the third phase the potentialities of the destination were evaluated by analyzing existing products and proposing new products. Finally, the marketing plan was designed and promotion strategies were proposed. It was evidenced that the destination presents deficiencies in various sectors from management, infrastructure, lack of investment and insufficient dissemination of tourism resources. Regarding the market, it was known that most of the attractions are of hierarchy III, there are various tourist establishments, the demand mostly visits Portoviejo for the gastronomy, foreign visitors are mainly Colombians and they obtain information through the internet. From the study of the potentialities, it was obtained as a result that the Crucita beach is the most potential place and new products have been evidenced. Finally, marketing mix strategies were established and programs and projects aimed at distribution channels, tourism brand, investment, positioning and tourism promotion of the canton were proposed. In conclusion, Portoviejo has favorable elements for the development and potentialization of tourism that can be promote through a digital marketing plan.